2017
DOI: 10.1021/acs.jpcc.7b00319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ring Strain on the Charge Transport of a Robust Norbornadiene–Quadricyclane-Based Molecular Photoswitch

Abstract: Integrating functional molecules into single-molecule devices is a key step toward the realization of future computing machines based on the smallest possible components. In this context, photoswitching molecules that can make a transition between high and low conductivity in response to light are attractive candidates. Here we present the synthesis and conductance properties of a new type of robust molecular photothermal switch based on the norbornadiene (NB)–quadricyclane (QC) system. The transport through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 47 publications
1
52
0
1
Order By: Relevance
“…Next, we showed that PC sorting can perform a very useful task: it can distinguish groups with a change in conductance of about half an order of magnitude and an associated change in plateau length of about 0.15 nm. Changes in conductance like this are common in optically [22] and electrochemically [23] switched SMBJs. Furthermore, 0.15 nm represents the radius of a gold atom and the bottom limit of measurable differences between groups.…”
Section: Use Policymentioning
confidence: 79%
“…Next, we showed that PC sorting can perform a very useful task: it can distinguish groups with a change in conductance of about half an order of magnitude and an associated change in plateau length of about 0.15 nm. Changes in conductance like this are common in optically [22] and electrochemically [23] switched SMBJs. Furthermore, 0.15 nm represents the radius of a gold atom and the bottom limit of measurable differences between groups.…”
Section: Use Policymentioning
confidence: 79%
“…With an increasing core-to-core distance of the porphyrins from 10.7 to 18.3 and 21.3 for the ortho-, meta-, and para-conjugates,r espectively,t hroughspace communication has only minor impact on the spectral features.H owever,t he situation is more distinct upon inspecting the molecular orbitals.A lthough most of the electron distribution of the highest occupied molecular orbital (HOMO) is located on the porphyrins,p art is also based on the HBC core.H ereby,t he conjugation pathway is found to go always across the middle ring of the HBC core.Inthe ortho case,t he communication takes an angular pathway through the HBC'sc entral ring, rather than through the biphenyl fragment. [23] Less pronounced, this indirect pathway is also true for the meta conjugate.O nt he other hand, para structures find their most direct communication through the middle of the HBC.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Molecular photoswitches have aroused widespread interest in recent years. [1][2][3][4][5] Because of their unique photochromic characteristics, 6 they have been widely used in molecular data storage, 7-9 photopharmacology, 10 optochemical genetics, 11 materials science, 12 and biomolecules 13,14 among other areas. Over the past few decades, most research has been focused on azobenzenes, 15 spiropyrans, 16 diarylethenes, 17 and stilbenes 18 which are all characterized by photoisomerization.…”
Section: Introductionmentioning
confidence: 99%